CINEMATIC REPRESENTATIONS OF PARTITION OF INDIA - Sharma, Manoj (PEOPLE: International Journal of Social Sciences, 2017)
The partition of India in August 1947 marks a watershed in the modern Indian history. The creation of two nations, India and Pakistan, was not only a geographical division but also widened the chasm in the hearts of the people. The objective of the paper is to study the cinematic representations of the experiences associated with the partition of India. The cinematic portrayal of fear generated by the partition violence and the terror accompanying it will also be examined. Films dealing with partition have common themes of displacement of thousands of masses from their homelands, being called refugees in their own homeland and their struggle for survival in refugee colonies. They showcase the trauma of fear, violence, personal pain, loss and uprooting from native place. Also, how the cinematic space tries to recreate those horrors, bestial passions and disregard for humanity in the larger political arena will also be examined. At the same time, sexuality and gender relations where women’s bodies became site of conflict between two communities will also be discussed. Moreover, how the personal experiences of filmmakers during the times of partition shaped their cinematic depictions will also be enumerated. Films which remind us of that communal carnage called partition, for instance, Lahore (1949, Hindi), Chhinamula (1951, Bengali) Megha Dhaka Tara (1960, Bengali), Subarnrekha (1965, Bengali) Garm Hawa (1973, Hindi), Tamas (1987, Hindi) Bombay (1995, Hindi), 1947 Earth (1998, Hindi), Gadar: Ek Prem Katha (1998) Fiza (2002, Hindi), Pinjar (2003, Hindi) Dev (2003, Hindi), Partition (2007, English) and Midnight Children (2012, English) will be examined.